Sleep characteristics, sleep problems, and associations of self-efficacy among German university students - Gulewitsch MD; Kulessa D; Schlarb AA (Nature and Science of Sleep, 2012)
Angelika A Schlarb1,2, Dominika Kulessa1,*, Marco D Gulewitsch1,*1Faculty of Science, Department of Psychology, University of Tübingen, 2Faculty of Psychology, University of Koblenz-Landau, Germany*These authors contributed equally to this workBackground: Sleep problems, especially insomnia, are a common complaint among adults. International studies on university students have shown prevalence rates between 4.7% and 36.2% for sleep difficulties, and 13.1% and 28.1% for insomnia. Sleep problems are associated with lower social and academic performance and can have a severe impact on psychological and physical health.Objective: The goal of this study was to outline sleep characteristics, prevalence of sleep problems, insomnia, and associations with self-efficacy among German university students.Methods: A total of 2196 university students (70.9% women; mean age 24.16 years) participated in the study. Sleep characteristics, sleep problems, insomnia, and self-efficacy were assessed using a questionnaire.Results and conclusion: Analyses revealed that more than 16% of surveyed students needed more than 30 minutes to fall asleep. About 7.7% of the students suffered from insomnia. Short sleep was significantly associated with a considerably increased rate of insomnia (20%). Insomniacs showed lower self-efficacy than students without sleep problems.Keywords: university students, sleep characteristics, sleep problems, insomnia, self-efficacy